Helminths from the Weddell seal, Leptonychotes weddelli (Lesson, 1826), in the Antarctic - Beverley-Burton, Mary (Canadian Journal of Zoology, 1971)
The alimentary tracts of seven Weddell seals taken at McMurdo Sound, Antarctica, were examined for helminth parasites. Two species of trematodes, three of cestodes, and one of nematodes were recovered. Numerical data on incidence and intensity of infection are given for each species. Heavy infections of diphyllobothriid plerocercoids were also recorded.